(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2025)
In recent years, additive manufacturing (AM) of metals gains more and more interest in the automotive and aerospace industries as well as medicine. Thus, the associated component analysis - especially with focus on safety aspects - has become increasingly important. In this context, the non-destructive evaluation of the porosity within the material and its minimization by optimization of AM-printing parameters are of great interest. In addition to overall porosity and density reduction, this study emphasizes the classification of pore types. This allows to categorize the material and accordingly improve the printing processes, where the combined usage of artificial intelligence (AI) opens the door for an efficient way of material development optimization.